Comparing Conservative Treatment With Antibiotics and Appendectomy for Acute Appendicitis in Adult: A Comprehensive Systematic Review - Agustina; Fenny (The International Journal of Medical Science and Health Research, 2024)
Background: Acute appendicitis is the most common reason for an emergency abdominal surgery, with a lifetime appendectomy risk of 12% for males and 23% for females. Although conservative (i.e., nonoperative) treatment of acute uncomplicated appendicitis with antibiotics has yet to be routinely recommended over appendectomy. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same              journal as the submission without a DOI were not accepted. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: For patients who do not have a strong desire for emergency surgery or refuse emergency surgery, a conservative treatment that mainly entails anti-infection may be temporary.